CURRENT STYLISTIC TRENDS IN UKRAINIAN MUSIC CREATION ON THE THEME OF WAR - Шакіров, Володимир (SWorldJournal, 2026)
The article examines the development of musical creativity on military themes from the perspective of identifying the stylistic basis in the compositional creativity of various genres and its development in line with various stylistic trends, which are de